Web-Based Library Information System at Maraqitta'limat Suela Vocational School - Pramartha, Yayan Eva; Muhamad Masjun Efendi (Alpatih Harapan Semesta, 2023)
This report contains the library information system with the study of SMK Maraqitta'limat Suela. The service procedure of the system is made in the form of a web-based library information system so that it changes the system of borrowing and returning books that were previously manual into computerized. Data collection methods used include field studies and literature studies. Field studies include observational studies or direct observations and direct interview methods with parties related to the problem under study in order to obtain reliable data and information. While the literature study is useful for obtaining a theoretical basis in the form of expert opinions regarding the object of research such as applicable laws and regulations relating to the matters being researched. With this information system, it is easier for library staff and teachers to carry out a series of processes for borrowing and returning books in the library from input to reporting processes. The conclusion of this report is that the library system becomes easier and faster because it uses a more dynamic web-based application. This system is still not in accordance with the needs and has not been implemented in the Maraqitta'limat Suela Vocational School.